1999
DOI: 10.1097/00007890-199910150-00025
|View full text |Cite
|
Sign up to set email alerts
|

Gemcitabine-a Novel Immunosuppressive Agent-Prevents Rejection in a Rat Cardiac Transplantation Model1

Abstract: DFdC is a new immunosuppressive agent that can successfully prevent cardiac rejection in a rat transplantation model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2008
2008

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…dFdC has already been widely used in humans as an anticancer drug because of its cytotoxic potential with few side effects. As an immunosuppressive drug, dFdC was successfully tested in a rat cardiac transplantation model to prevent GVHD (12). In these rats, however, dFdC was started even before cardiac transplantation, ensuring higher levels of dFdC during the onset of GVHD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…dFdC has already been widely used in humans as an anticancer drug because of its cytotoxic potential with few side effects. As an immunosuppressive drug, dFdC was successfully tested in a rat cardiac transplantation model to prevent GVHD (12). In these rats, however, dFdC was started even before cardiac transplantation, ensuring higher levels of dFdC during the onset of GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…As a cytotoxic agent, dFdC is widely used for the treatment of solid malignancies and refractory hematologic malignancies (9,10). Besides, in vitro studies revealed an inhibitory effect of dFdC on lymphocytes and bone marrow progenitors (11), and an immunosuppressive effect was described in a rat cardiac transplantation model (12). Therefore, we hypothesized that dFdC may also be a promising alternative for treatment of ABD lesions.…”
Section: Introductionmentioning
confidence: 99%
“…One of these agents could be gemcitabine, a drug showing, at standard cytotoxic dose, relatively low total toxicity. Its immunosuppressive action was first assessed by a team headed by Margreiter [3] in a model of heart transplantation in the rat, with encouraging preliminary results. They confirmed the hypothesis that multiple administration of low-dose dFdC has a primary effect on immunocompetent cells.…”
Section: Discussionmentioning
confidence: 99%
“…Initial studies on the effects of the drug in lymphocyte colony-forming assays showed that the drug inhibited the PHA-induced lymphocyte proliferation in vitro and that it prolonged significantly the survival of rats implanted an allogeneic heart [236]. Gemcitabine (2,2'difluorodeoxycytidine) (dFdC) is an antimetabolite which is useful in the treatment of pancreatic cancer.…”
Section: Fluorouracil (5fu)mentioning
confidence: 99%